Rediscovery and new combination of Serpocaulon demissum (Polypodiaceae), an endangered endemic species to the Brazilian inselbergs - Sanín, David; Salino, Alexandre (Phytotaxa, 2020)
Serpocaulon demissum is herein proposed as a new combination based on the study of the type specimens and protologue of Goniophlebium demissum, as well as the comparison with its sympatric and morphologically similar species, S. catharinae and S. vacillans, two widespread species from the Atlantic Forest. Serpocaulon demissum is similar to these species by the presence of patent rhizomes scales and pinnatisect laminae, but differs from them by its thick amylaceous rhizomes, larger rhizome scales, and spores without folded perine. This taxon represents an endemic species from the Brazilian inselbergs. A re-description that includes a lectotype designation, line drawings, SEM pictures of the spores, pictures of the plant in the field, information of the novel habitat and rhizome stores, distribution map, and the conservation status of the species is presented.